How habitat heterogeneity shapes bacterial and protistan communities in temperate coastal areas near estuaries. (12th January 2022) - Zhao, Zelong; Li, Hongjun; Sun, Yi; Shao, Kuishuang; Wang, Xiaocheng; Ma, Xindong; Hu, Anyi; Zhang, Haikun; Fan, Jinfeng
Summary: In this study, we investigated microbial communities (bacteria and protist) in two coastal areas near the estuaries of the Liaohe (LH) River and Yalujiang (YLJ) River in the Northwestern Pacific Ocean. Due to the existence of Liaodong Peninsula and different levels of urbanization, geographical segregation and significant environmental heterogeneity were observed between these two areas. There were significantly different regional species pools and biogeographic patterns for both bacterial and protistan communities between LH and YLJ coastal areas. Species turnover was the main mechanism driving β‐diversity patterns of both bacterial and protistan communities in each area. In addition, the contributed ratio of nestedness to the β‐diversity patterns was significantly higher for protists compared to bacteria. Variation in regional species pools was found to be the dominant driver of differences of bacterial and protistan communities between the LH and YLJ coastal areas. For a single‐studied area, local community assembly mechanisms, including heterogeneous selection and dispersal limitation, were found to shape the bacterial and protistan communities through calculation of the β‐deviation index. Among them, the relative importance of heterogeneous selection and dispersal limitation on the community assembly varied according to microorganism type and habitat.